2020
DOI: 10.1016/j.apsb.2019.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Limitation standard of toxic aconitines in Aconitum proprietary Chinese medicines using on-line extraction electrospray ionization mass spectrometry

Abstract: Development of rapid analytical methods and establishment of toxic component limitation standards are of great importance in quality control of traditional Chinese medicine. Herein, an on-line extraction electrospray ionization mass spectrometry (oEESI-MS) coupled with a novel whole process integral quantification strategy was developed and applied to direct determination of nine key aconitine-type alkaloids in 20 Aconitum proprietary Chinese medicines (APCMs). Multi-type dosage forms ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Linear regression analysis was conducted for each compound to obtain a calibration curve and correlation coefficient (R 2 ) with all the triple repeated data by plotting the peak area (Y) versus the concentration (X) for each analyte. The limit of detection (LOD) and limit of quantitation (LOQ) were determined as the concentration that reached the signal-to-noise ratio of 3 and 10, respectively (Qiu et al, 2019). A standard working solution of a middleconcentration sample was analyzed in six replicates within 1 day and in three replicates on three consecutive days; relative standard deviation (RSD) was applied to evaluate intra-and inter-day precision.…”
Section: Methods Validation Of Quantitative Analysismentioning
confidence: 99%
“…Linear regression analysis was conducted for each compound to obtain a calibration curve and correlation coefficient (R 2 ) with all the triple repeated data by plotting the peak area (Y) versus the concentration (X) for each analyte. The limit of detection (LOD) and limit of quantitation (LOQ) were determined as the concentration that reached the signal-to-noise ratio of 3 and 10, respectively (Qiu et al, 2019). A standard working solution of a middleconcentration sample was analyzed in six replicates within 1 day and in three replicates on three consecutive days; relative standard deviation (RSD) was applied to evaluate intra-and inter-day precision.…”
Section: Methods Validation Of Quantitative Analysismentioning
confidence: 99%
“…The minimum toxic doses of mesaconitine and hypaconitine in humans have been reported as 0.0035 and 0.0162 mg/kg, respectively ( Qiu et al, 2020b ), which can be converted to 21.88 and 101.25 μg/kg in rats ( Huang et al, 2004 ). The doses of the two diester alkaloids in this experiment were 0.34 μg/kg for mesaconitine and 11.86 μg/kg for hypaconitine in Fuzi decoction, and 1.80 μg/kg for mesaconitine and 87.03 μg/kg for hypaconitine in Shenfu decoction.…”
Section: Resultsmentioning
confidence: 99%
“…The doses of the two diester alkaloids in this experiment were 0.34 μg/kg for mesaconitine and 11.86 μg/kg for hypaconitine in Fuzi decoction, and 1.80 μg/kg for mesaconitine and 87.03 μg/kg for hypaconitine in Shenfu decoction. After the application of our developed toxicity prediction method ( Qiu et al, 2020a ; Qiu et al, 2020b ), it was found that the in vivo holistic weighted toxicity (HWT) value was less than 1, indicating all alkaloids were below the minimum toxic doses. Therefore, the three diester alkaloids showed no toxicity but only medicinal effects under the present conditions.…”
Section: Resultsmentioning
confidence: 99%
“…[27][28][29][30][31][32] These AI-MS techniques are now widely used for the analysis of Chinese medicine. [33][34][35][36][37] The quality of Chinese herbal medicines is determined by multiple factors, such as planting/breeding, harvesting, processing, production, logistics and marketing. The development of a quality evaluation method for CHMs based on portable MS will contribute to the whole-process quality control and traceability of CHMs.…”
Section: Introductionmentioning
confidence: 99%